Parametrização e movimentação de curvas e superfícies para uso em Modelação Matemática - Paranhos, Marcos de Miranda (2015)
This research is themed content traditionally taught in mathematical disciplines of Higher Education. The curves and surfaces studied in the Differential and Integral Calculus and Analytic Geometry and transformations of Linear Algebra are some content. The proposed question is what are the development of systematic activities possibilities, articulation and application of mathematical objects studied in the disciplines of CDI, GA and AL, for further study of these subjects? It was the way they are taught to present deepening proposals, articulation and application thereof, in view of Mathematical Modelling in order to enhance the results achieved in their learning and use. Were developed using the methodology of Didactic Engineering Mathematical Modelling activities in computational environment to be worked with students who have studied these disciplines. In the first stage there were four proposed activities to familiarize the student with the parameterization of curves and surfaces, with the changes and using the Winplot software. This step aimed to enable students to describe and move objects of reality in computing environment, using expressions and objects of mathematics. In the second stage, were proposed four activities to reproduce situations of reality, which can be expressed and modified by means of mathematical objects studied and modeled in the first stage. The forms of work presented in the survey do not dispense what is already done, but have favorable prospects especially in two respects: the depth that can be given to the objects studied, bringing difficult issues to deal with in other contexts, and in the form of work shown enjoyable and stimulating